2017
DOI: 10.1186/s40478-017-0498-5
|View full text |Cite
|
Sign up to set email alerts
|

MUNC18–1 gene abnormalities are involved in neurodevelopmental disorders through defective cortical architecture during brain development

Abstract: While Munc18–1 interacts with Syntaxin1 and controls the formation of soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNARE) complex to regulate presynaptic vesicle fusion in developed neurons, this molecule is likely to be involved in brain development since its gene abnormalities cause early infantile epileptic encephalopathy with suppression-burst (Ohtahara syndrome), neonatal epileptic encephalopathy and other neurodevelopmental disorders. We thus analyzed physiological significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…We propose that a comparative analysis based on MD simulations for calculating the deviation in protein-protein interaction energy, be applied to other complexes for which high-resolution X-ray structures are available. (Hamada, Iwamoto, Tabata, & Nagata, 2017). However, in the patient reported in this study, no brain developmental or structural alterations were observed, thus F I G U R E 5 Model for STXBP1 pathology and clinical manifestation of R39dup mutant protein.…”
Section: Discussionmentioning
confidence: 54%
“…We propose that a comparative analysis based on MD simulations for calculating the deviation in protein-protein interaction energy, be applied to other complexes for which high-resolution X-ray structures are available. (Hamada, Iwamoto, Tabata, & Nagata, 2017). However, in the patient reported in this study, no brain developmental or structural alterations were observed, thus F I G U R E 5 Model for STXBP1 pathology and clinical manifestation of R39dup mutant protein.…”
Section: Discussionmentioning
confidence: 54%
“…Then, gentle dissociation of neuronal cells was performed with trypsin (0.25%) and mechanical disruption was done to separate cells from connective tissue while providing minimum damage to individual neuronal cells [ 19 ]. The isolated neurons were cultured essentially as described [ 3 , 6 ]. Transient transfection was carried out using Lipofectamine 2000 (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Examples of mucus release components that overlap with synaptic neurotransmitter systems include syntaxin, Munc 18, VAMP, and SNAP proteins. These vesicleassociated proteins are commonly expressed at neuronal synaptic membranes and have been identified as being mutated in neurological disorders (syntaxin; ASD, SNAP; ADHD, Munc 18; epilepsy/ASD (Guerini et al, 2011;Durdiaková et al, 2014;Hamada et al, 2017). Changes in the function of these proteins will not only contribute to brain disorders but may also disrupt vesicular secretion of mucus.…”
Section: Vesicle-associated Proteinsmentioning
confidence: 99%